Broadband Phase-Sensitive Single InP Nanowire Photoconductive Terahertz Detectors - Peng, K; Parkinson, P; Boland, J; Gao, Q; Wenas, Y; Davies, C; Li, Z; Fu, L; Johnston, M; Tan, H; Jagadish, C (American Chemical Society, 2016)
Terahertz time-domain spectroscopy (THz-TDS) has emerged as a powerful tool for materials characterization and imaging. A trend toward size reduction, higher component integration, and performance improvement for advanced THz-TDS systems is of increasing interest. The use of single semiconducting nanowires for terahertz (THz) detection is a nascent field that has great potential to realize future highly integrated THz systems. In order to develop such components, optimized material optoelectronic properties and careful device design are necessary. Here, we present antenna-optimized photoconductive detectors based on single InP nanowires with superior properties of high carrier mobility (∼1260 cm2 V-1 s-1) and low dark current (∼10 pA), which exhibit excellent sensitivity and broadband performance. We demonstrate that these nanowire THz detectors can provide high quality time-domain spectra for materials characterization in a THz-TDS system, a critical step toward future application in advanced THz-TDS system with high spectral and spatial resolution.